KENDALA INVESTASI DI ERA OTONOMI DAERAH (Studi Kasus Pembangunan Proyek PLTU di Kabupaten Batang) - ISMAIL, ISA (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Research that was headlined investment in Regional Autonomy era ( case study constraint the construction of PLTU project in the Batang Regency) is done using analysis of Pustaka about the concept of investment and the concept of regional autonomy. The study is done with the methodology of some research qualitative descriptive with purposive of sampling techniques in determining an informer and continues to be a snowball of sampling. Obtained data in field indicates that central program of government included in the program Master Plan for Acceleration and Expansion of Indonesia's Economic Development (MP3EI). The program of PLTU in Batang Regency worth more or less 38 trillion. Realization of PLTU project development was delayed for two years since the early planning. The delay of PLTU project has several problems, among others, such as lack of coordination between the central government and local governments, investors, a policy that overlap related regulations of marine conservation issued by regent, and the land acquisition process experiencing self denial of the owner of the land. Attempt completion constraint is still done through personal approaches between the local Government to the Government of the village, between the Government of the village with its citizens, especially the owner of the land where the project will be built and efforts in corporate social responsibility (CSR) by the investors realization with the construction of various public facilities to affected communities